Pengaruh Penggunaan Gadget Terhadap Produktivitas Belajar Mahasiswa dan Kecerdasan Emosional Mahasiswa - Wijayanti, Wanda; Efendi, Riyanto; Hudha, Choirul; Kusumawati, Astrian; Indarto, Vicky (PT. Alahyan Publisher Sukabumi, 2025)
This study examines how device usage affects emotional intelligence and learning productivity at the Economy Education, University of Jember. Data were collected through questionnaires distributed to 127 students and then analyzed using descriptive statistics to identify device usage patterns and their relationship to emotional intelligence and learning productivity. The results showed that excessive use of electronic devices negatively correlated with students' learning productivity and emotional intelligence, particularly in terms of emotional control and learning focus. In conclusion, students must be able to properly control their use of electronic devices if they want to maintain their emotional intelligence and improve their learning productivity.